27.1k views
2 votes
2 expressions equivalent to (x-6) • (x-3)

User Dinho
by
5.5k points

1 Answer

3 votes

Answer:

x^2 + -9 x + 18 = (x - 9) x + 18 = (x - 6) (x - 3) all three are alternanate forms.

Explanation:

Expand the following:

(x - 6) (x - 3)

Hint: | Multiply x - 6 and x - 3 together using FOIL.

(x - 6) (x - 3) = (x) (x) + (x) (-3) + (-6) (x) + (-6) (-3):

x x - 3 x - 6 x - 6 (-3)

Hint: | Combine products of like terms.

x x = x^2:

x^2 - 3 x - 6 x - 6 (-3)

Hint: | Multiply -6 and -3 together.

-6 (-3) = 18:

x^2 - 3 x - 6 x + 18

Hint: | Group like terms in x^2 - 3 x - 6 x + 18.

Grouping like terms, x^2 - 3 x - 6 x + 18 = x^2 + (-3 x - 6 x) + 18:

x^2 + (-3 x - 6 x) + 18

Hint: | Combine like terms in -3 x - 6 x.

-3 x - 6 x = -9 x:

Answer: x^2 + -9 x + 18 = (x - 9) x + 18 =(x - 6) (x - 3)

User Tlaminator
by
5.1k points